Thinking Globally, Composing Locally : Rethinking Online Writing in the Age of the Global Internet - St. Amant, Kirk, 1970-; Rice, Rich (Richard Aaron) (Book collections on Project MUSE., 2018)
"How writing and its pedagogy should adapt to the ever-expanding environment of international online communication. A global audience presents many challenges: writers seeking to contact and connect with individuals from different cultures must rethink their concept of audience, but prepare to address friction from cross-cultural rhetorical situations"--Provided by publisher